Investigation on the static and dynamic structural behaviors of a regional aircraft main landing gear by a new numerical methodology (Fracture and Structural Integrity, 2017)
In this paper, a new methodology supporting the design of landing gears is proposed. Generally, a preliminary step is performed with simplified FE model, usually one-dimensional, to achieve the reaction forces involving each component during all aforementioned aircraft operations. Though this approach gives a valid support to the designer, it is characterized by several problems, such as the related approximations. So, it is important, by a numerical point of view, to develop an isostatic FE model equivalent to the real one. In fact, if the landing gear is modelled as hyperstatic, the static equilibrium equations are insufficient for determining the internal forces and reactions on each sub-component; so, the modelled material properties and geometries assume an increasing importance, which gets the model too approximating. The proposed methodology consists of achieving the reaction forces by means of multibody simulations, by overcoming such problems, since each component is modelled as rigid. In this paper, also a FE model for the investigation of the structural response is proposed. Aimed to Certification by Analysis purposes, the developed multibody and the FE models have been assessed against an experimental landing gear drop test carried out by Magnaghi Aeronautica S.p.A., according to the EASA CS 25 regulations.
Keywords: Landing gear; Multibody; FE analysis; Dynamic behaviour; Drop Test